Technical Efficiency of Thermal Electricity Generators in Kenya - Njeru, Grace; Gathiaka, John; Kimuyu, Peter (International Journal of Energy Economics and Policy, 2020)
The Government of Kenya introduced energy sector reforms in the late 1990s aimed at improving efficiency in the supply of energy. After over two decades of reforms, there has been no comprehensive study to estimate the technical efficiency amongst electricity generators in Kenya. This study examined 27 thermal electricity generating plants in Kenya using data sourced from Energy Regulation Commission for the period July 2015 to December 2017. The study applied two methods to estimate efficiency, viz., the Stochastic Frontier Analysis and Data Envelope Analysis. The results indicated that there is inefficiency in thermal power generation. The average efficiency score was 71% meaning the industry was missing its technical potential by about 29%. The plants experienced increasing returns to scale and were improving on efficiency and productivity. Age and public ownership contributed to inefficiency while grid connection had a positive effect on efficiency. The government should encourage private investment in future power generation projects while at the same time increasing connection of the isolated areas to the national grid. The regulator should also revisit the current specific fuel targets used in determining the fuel pass through costs to consumers to encourage efficiency. Keywords: Technical efficiency; Electricity Generation; SFA; DEA; Kenya JEL Classifications: D24, L11, L25 DOI: https://doi.org/10.32479/ijeep.9102